2019
DOI: 10.20429/ijsotl.2019.130208
|View full text |Cite
|
Sign up to set email alerts
|

First Semester Academic Functioning of College Students: The Role of Stressful and Traumatic Life Events

Abstract: The present study sought to better understand the role of stress and trauma history and resiliency among students from low socioeconomic backgrounds and their college academic outcomes. Self-reported history of stressful and traumatic life events, resilience, and demographic factors were collected at orientation for 54 "poor" students as determined by Federal standards. Academic record information was collected at the end of the first semester. The study sample was similar to other students in terms of event e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Further, nearly 26% of college students reported that within the past 12 months, they had a personal health issue that was "traumatic or difficult to handle" (ACHA, 2019). This is particularly problematic when considering that exposure to traumatic or difficult events is associated with withdrawing from courses, failing grades, and lower grade point averages, particularly among students from low-income backgrounds (Warnecke & Lewine, 2019). More broadly, mental health issues such as depression and anxiety affect students' ability to perform well in college and reduce the likelihood of graduation (Eisenberg, Downs, Golberstein, & Zivin, 2009;Mojtabai et al, 2015).…”
Section: Orcidmentioning
confidence: 99%
“…Further, nearly 26% of college students reported that within the past 12 months, they had a personal health issue that was "traumatic or difficult to handle" (ACHA, 2019). This is particularly problematic when considering that exposure to traumatic or difficult events is associated with withdrawing from courses, failing grades, and lower grade point averages, particularly among students from low-income backgrounds (Warnecke & Lewine, 2019). More broadly, mental health issues such as depression and anxiety affect students' ability to perform well in college and reduce the likelihood of graduation (Eisenberg, Downs, Golberstein, & Zivin, 2009;Mojtabai et al, 2015).…”
Section: Orcidmentioning
confidence: 99%
“…Anxiety has a direct negative impact on QOL, and academic stress has a direct poor impact as well [55]. Students' encounters with more recent traumatic incidents are also significantly related to low retention and grades at university [56]. Previous research has discovered a link between anxiety levels and QOL.…”
Section: Anxiety and The Qolmentioning
confidence: 99%
“…(2) How will receiving a college degree impact your future? Questionnaire (sociodemographic information, life events, affect, cognitive style) packets were distributed and completed during orienta-tion week for those students admitted to the university and entering the CCP (see Davis, 2017;Warnecke, 2017 for full details of the study). Term GPA was obtained from student academic transcripts at the end of the first semester.…”
Section: Participantsmentioning
confidence: 99%